Nursing service innovation: A case study examining emergency nurse practitioner service sustainability. (19th October 2017) - Fox, Amanda; Gardner, Glenn; Osborne, Sonya
Abstract: Aim: This research aimed to explore factors that influence sustainability of health service innovation, specifically emergency nurse practitioner service. Background: Planning for cost effective provision of healthcare services is a concern globally. Reform initiatives are implemented often incorporating expanding scope of practice for health professionals and innovative service delivery models. Introducing new models is costly in both human and financial resources and therefore understanding factors influencing sustainability is imperative to viable service provision. Design: This research used case study methodology (Yin, 2014 ). Methods: Data were collected during 2014 from emergency nurse practitioners, emergency department multidisciplinary team members and documents related to nurse practitioner services. Collection methods included telephone and semi‐structured interviews, survey and document analysis. Pattern matching techniques were used to compare findings with study propositions. Findings: In this study, emergency nurse practitioner services did not meet factors that support health service sustainability. Multidisciplinary team members were confident that emergency nurse practitioner services were safe and helped to meet population health needs. Organizational support for integration of nurse practitioner services was marginal and led to poor understanding of service capability and underuse. Conclusion: This research provides evidence informing sustainability of nursing service models but more importantly raises questions about this little explored field. The findings highlight poor organizational support, excessive restrictions and underuse of the service. This is in direct contrast to contemporary expanding practice reform initiatives. Organizational support for integration is imperative to future service sustainability.